A Freirean perspective on South African teacher education policy development - Botman, B.V. (South African Journal of Higher Education, 2016)
This article discusses the importance of teacher education and why Freire is an appropriate interlocutor. Freire believes that in order to become a teacher one needs to engage in the acts of studying, teaching, learning, knowing, knowledge creation and entertainment. The article describes and analyses policy on restructuring teacher education of the four democratic administrations culminating in policy. An analysis of the Policy on Minimum Requirements for Teacher Education, Qualifications and the corresponding Strategic Planning Framework includes the goals, principles, outputs and outcome, philosophy and pedagogy, as well as participatory structures. The argument is that South African teacher education policy can draw on Freirean education philosophy in order to develop explicit goals, principles, structures, philosophy and pedagogy necessary for transformation in education, in line with the responsibilities placed on teacher education through the National Development Plan.